Effects of different industrial waste materials as partial replacement of fine aggregate on strength and microstructure properties of concrete. (March 2021) - Kaish, A.B.M.A.; Odimegwu, Temple Chimuanya; Zakaria, Ideris; Abood, Manal Mohsen
Abstract: This study aimed at investigating the effect of different industrial waste material as partial replacement of fine aggregate on strength properties of normal concrete. For economical and sustainability of natural resources, use of some industrial waste can demonstrate numerous benefits for the construction industry. Nevertheless, there is limited study on the use of industrial waste as replacement of fine aggregate in normal strength concrete especially, using alum sludge from water treatment plant as replacement of fine aggregate. The material used in this study as replacement of fine aggregate (river sand) was oven-dried alum sludge. While quarry dust and limestone dust were also employed as non-reactive industrial waste material, to identify the specific effect of oven-dried alum sludge in concrete. All the materials were crushed to obtain smaller particle size and then used as replacement of fine aggregate in different percentages (5, 10 and 15%). The results from the experiments shows that addition of industrial waste material improved the concrete density, compressive, flexural, and splitting tensile strengths. The result also shows that optimum replacement content of fine aggregate with industrial waste were 10% for oven-dried alum sludge, whereas 15% for quarry and limestone dust content that improved all strength properties investigated in this study. All industrial waste employed in this study as fine aggregate have proven to be a good filler material by filling the concrete internal void and improving the strength properties for a normal strength concrete.